Medical experiments between the necessity of scientific progress and ensuring human safety (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Most laws tend to regulate provisions relating to medical experiments on humans. Therefore, this study deals with explaining the concept of medical experiments, and the suitability and adequacy of these provisions in ensuring protection for the person subject to the medical experiment, whether he is a patient or a volunteer.The Syrian legislator has issued a law related to pharmaceutical studies, but there is no special law regulating the subject of medical experiments. Therefore, this research suggests the necessity of enacting a law regarding medical experiments and the liability resulting from them.